Juvenile Sentencing Policy in Cases of Unauthorized Possession of Sharp Weapons: A Study of North Jakarta District Court Judgment 2024–2025 - Ivanly, Ivanly; Tunjung Sekartaji, Raden Rara Hapsari (Kadiri Islamic University, 2025)
This research is motivated by the complexity of handling cases of unauthorized possession of sharp weapons by juveniles in conflict with the law. The normative conflict between the repressive Emergency Law No. 12 of 1951 and the restorative Juvenile Criminal Justice System Law has led to inconsistencies in court judgment and legal uncertainty. This study aims to analyze the current sentencing policy in addressing such criminal acts. The method used is normative juridical with a statutory approach and case approach (analysis of North Jakarta District Court judgment 2024–2025), as well as qualitative analysis of primary, secondary, and tertiary legal materials. The results show disparities in case rulings and weak standard guidelines for imposing sanctions: some juveniles were sentenced to social institution rehabilitation or vocational training, while others were simply returned to their parents. This disparity creates legal uncertainty for juveniles as offenders, since similar cases are treated differently without clear criteria. In conclusion, the current sentencing policy has not consistently applied the principles of restorative justice and ultimum remedium, thus harmonization of legislation and clear guidelines are needed to ensure legal protection for children.